Design and implementation of a water treatment system using ultraviolet radiation (UV) produced with photovoltaic energy - Ramírez Revilla, Stamber Alvaro (2021)
The objective of this research study was to design and implement a water treatment system using ultraviolet radiation (UV)produced with photovoltaic panels. This system would be able to satisfy the needs of residents who do not have drinking waterand live in rural areas. The design begins with the evaluation of the energy demand required for the ultraviolet light lamp and thewater pump, which are powered by the photovoltaic panel. The system consists of a tank for water collection, a DC12V pump, apre-filter and a filter for sediments, an activated carbon filter, a UV-C light lamp and a storage tank. Mandatory control parametersaccording to DIGESA were evaluated such as pH, color, turbidity, thermotolerant and total coliforms present in the water, beforeand after the treatment. The results obtained demonstrate that the system works efficiently. The observed values were lower thanthe maximum permissible limits for the physicochemical and microbiological analysis. For total and thermotolerant coliforms,0 CFU/100 mL were found, demonstrating that UV-C radiation completely eliminates the microorganisms present in water.